Empirical Bayes Methods for Dynamic Factor Models - Siem Jan Koopman; Geert Mesters (Tinbergen Institute, 2014)
We consider the dynamic factor model where the loading matrix, the dynamic factors and the disturbances are treated as latent stochastic processes. We present empirical Bayes methods that enable the efficient shrinkage-based estimation of the loadings and the factors. We show that our estimates have lower quadratic loss compared to the standard maximum likelihood estimates. We investigate the methods in a Monte Carlo study where we document the finite sample properties. Finally, we present and discuss the results of an empirical study concerning the forecasting of U.S. macroeconomic time series using our empirical Bayes methods.
Keywords: C32; C43; 330; Importance sampling; Kalman filtering; Likelihood-based analysis; Posterior modes; Rao-Blackwellization; Shrinkage